2007
DOI: 10.1634/stemcells.2007-0445
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oxygenation Promotes β-Cell Differentiation In Vitro

Abstract: STEM CELLS 2007;25: 3155-3164 Disclosure of potential conflicts of interest is found at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 82 publications
3
73
0
Order By: Relevance
“…It is important to mimic the in vivo developmental stages of pancreatic organogenesis in which cells are transitioned through mesendoderm, definitive endoderm, foregut endoderm, pancreatic progenitor, and the endocrine progenitor stage, until mature ␤-cells are obtained from pluripotent stem cells (38). Oxygen tension, the partial pressure of oxygen, has been shown to regulate the stem cell function and embryonic development of several organs, including the pancreas (9,10,(15)(16)(17)(18)(19)(20)(21)(22)(23). In the present study, we demonstrated that a high O 2 condition during the in vitro differentiation of ESC and iPSC has a facilitative effect on generating pancreatic progenitors and insulin-producing cells.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It is important to mimic the in vivo developmental stages of pancreatic organogenesis in which cells are transitioned through mesendoderm, definitive endoderm, foregut endoderm, pancreatic progenitor, and the endocrine progenitor stage, until mature ␤-cells are obtained from pluripotent stem cells (38). Oxygen tension, the partial pressure of oxygen, has been shown to regulate the stem cell function and embryonic development of several organs, including the pancreas (9,10,(15)(16)(17)(18)(19)(20)(21)(22)(23). In the present study, we demonstrated that a high O 2 condition during the in vitro differentiation of ESC and iPSC has a facilitative effect on generating pancreatic progenitors and insulin-producing cells.…”
Section: Discussionsupporting
confidence: 53%
“…The embryonic pancreas early in development is poorly vascularized and has a paucity of blood flow, and, at later stages, blood flow increases, and endocrine differentiation occurs at the same time (21). It has also been shown that HIF-1␣ protein is highly expressed in the embryonic pancreas early in development and that increasing concentrations of O 2 in vitro represses HIF-1␣ expression and fosters the development of endocrine progenitors (22,23). Suitable O 2 concentrations should be tested for the differentiation efficiency of ESC and iPSC into pancreatic lineages.…”
mentioning
confidence: 99%
“…In addition, hypoxia has been shown to inhibit differentiation of pancreatic b cells (26) and myoblasts (29) via interaction with the Notch signaling pathway. Taken together, these data suggest that submersion and hypoxia potentiate Notch signaling to repress the induction of genes necessary for ciliated cell development as diagrammed in Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that O 2 concentration at the level of the cells decreases as the apical media volume is increased (24,25). In addition, hypoxic conditions inhibit differentiation of different cell types (26)(27)(28)(29). Therefore, we hypothesized that submersion at greater apical media volumes creates a hypoxic environment that inhibits ciliated cell differentiation.…”
Section: Hypoxia Inhibits Ciliated Cell Differentiationmentioning
confidence: 96%
“…We have shown, for instance, that molecular oxygen is a critical determinant of β-cell differentiation. 45 The design of novel culture devices to improve oxygen delivery (thus enhancing differentiation of stem cells into insulin-producing cells) is one example of the fruitful crosspollination between molecular biology and biophysical disciplines (see Figure 3). As the molecular environment is only one part of the equation of islet differentiation, replacement is just the most visible facet of any future cure for U S E N D O C R I N E D I S E A S E 2 0 0 7 type I diabetes.…”
mentioning
confidence: 99%